2013
DOI: 10.1021/jf3042825
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolics Composition of the Leaves of Zanthoxylum bungeanum Maxim. Grown in Hebei, China, and Their Radical Scavenging Activities

Abstract: High performance liquid chromatography coupled with tandem mass spectrometry with electrospray ionization and negative ion detection (HPLC-ESI-MS/MS) was used to identify the polyphenols from the leaves of a traditional vegetable and spice, Zanthoxylum bungeanum Maxim., in China by comparison of the retention times and mass spectral fragment with standard substances or related literature. A phenolic acid glucoside, two acids, and eight flavonoids were determined including vanillic acid-4-glucoside (22.75 μg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 34 publications
3
85
2
2
Order By: Relevance
“…The leaves were cleaned, dried at 40 C for 2 h, ground to approximately 40 mesh and then vacuum-packed and stored at room temperature. The polyphenols were extracted as described by Yang et al (2013). The ground samples were extracted with a 65% (v/v) ethanol solution using a microwaveassisted extraction method.…”
Section: Preparation Of Zml Extractmentioning
confidence: 99%
See 2 more Smart Citations
“…The leaves were cleaned, dried at 40 C for 2 h, ground to approximately 40 mesh and then vacuum-packed and stored at room temperature. The polyphenols were extracted as described by Yang et al (2013). The ground samples were extracted with a 65% (v/v) ethanol solution using a microwaveassisted extraction method.…”
Section: Preparation Of Zml Extractmentioning
confidence: 99%
“…The scavenging activity was determined as described by Yang et al (2013), and the result was expressed as scavenging rate% The analysis was performed in triplicate.…”
Section: Dpph Free Radical Scavenging Activity Of Zml Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…They almost gave the same MS/MS fragments at m/z 301, revealing that they are quercetin derivatives with one sugar unit. It was previously reported that quercetin derivatives were the main flavonoids in Z. bungeanum fruits [9] and Z. bungeanum leaf, grown in Hubei [31]. Thus, we identified compounds 6 and 8 to be feoniculin and quercitrin, respectively.…”
Section: Identification and Quantificationmentioning
confidence: 68%
“…Maqian is frequently used as a spice for roasting and salting meat, boiling fish and cooking vegetable [3][4][5]. Many Zanthoxylum species used as medicines and spices around the world have been reported to have antioxidant activity and hepatoprotective activity [6][7][8]. Therefore, the purpose of this study was to assess the antioxidant activity and hepatoprotective effect of MQEO in STZinduced diabetic mice.…”
Section: Introductionmentioning
confidence: 99%